New treatments for opiate dependence - Stine, Susan M.; Kosten, Thomas R. (The Guilford substance abuse series, 1997)
Introduction and overview / Thomas R. Kosten and Susan M. Stine Part I. Foundations for the new interventions * Behavioral models of opiate abuse in animals / Therese A. Kosten * Basic neurobiology of opiate addiction / Eric J. Nestler Part II. Optimizing traditional treatments Section A. Refining the use of pharmacotherapy * New developments in methadone treatment and matching treatments to patients / Susan M. Stine * Use of pharmacological agents in opiate detoxification / Marc Rosen * Naltrexone and opiate abuse / Conor K. Farren, Stephanie O'Malley and Bruce Rounsaville * Comorbid substance abuse in opiate-dependent patients / Beatrice Burns Section B. Ancillary services and special populations * Matching methadone-maintained patients to psychosocial treatments / S. Kelly Avants, Robert Ohlin and Arthur Margolin * Acupuncture for cocaine abuse: Research findings, methodological issues, and patient-treatment matching / Arthur Margolin and S. Kelly Avants * Women and opiate dependence / Grace Chang * Medical issues in the care of opioid-dependent patients / Patrick G. O'Connor and Peter A. Selwyn Part III. The new pharmacotherapies * Opiate maintenance therapy with LAAM / Walter Ling and Peggy Compton * Buprenorphine / Alison Oliveto and Thomas R. Kosten Conclusions and future directions in treatment matching / Thomas R. Kosten